Left Ventricular Filling Pressure Assessed by Doppler Echocardiography as a Predictor of Inhospital Outcome in Patients of ST-segment Elevation Myocardial Infarction - Saha, Sumon Kumar; Ali, Mahboob; Rahman, Mohammad Arifur; Choudhury, Amal Kumar; Ulubbi, Salahuddin (Cardiovascular Journal, 2015)
Background: Left ventricular (LV) filling pressure is an important predictor of short and long term outcome in patients with coronary artery disease. Non invasive assessment of this pressure by Doppler echocardiography provides valuable information regarding the prognosis of patient with ST-segment elevation myocardial infarction. Elevated filling pressure is associated with increased incidence of morbidly and mortality due to ventricular remodeling, neuro-hormonal activation & increased excitability. The aim of this study was to assess LV diastolic dysfunction and left ventricular filling pressure in patients of ST-segment elevation myocardial infarction to predict their in-hospital outcome. Methods: The prognostic cohort study was conducted in National Institute of Cardiovascular Diseases, Dhaka from May 2011 to November 2011. A total of 100 Patients with acute ST-segment elevation myocardial infarction who has received streptokinase therapy were enrolled by purposive sampling. In addition to normal 2D & M mode study, Pulsed wave Doppler assessment of mitral valve inflow patterns was done in apical 4-chamber view to see Peak early (E) and peak late (A) flow velocities, E/A ratio and deceleration time of early mitral flow velocity (DT). Tissue Doppler Imaging (TDI) assessment was done at the lateral mitral annulus in apical 4-chamber view to assess Mitral annular diastolic velocity (E?) and E/E? ratio. Patients were divided into two groups based on Doppler echocardiography derived Left ventricular filling characteristics. In group I 50 patients with E/E? ratio <15 and in group II 50 patients with E/E >15. Patients were followed up for next 7 days and in-hospital outcomes were compared between groups. Results: The mean age of group-I & II were 53.84 ± 9.2 & 55.14 ± 8.5 years respectively. Male female ratio was 8.9:1.1. Age, sex and risk factors between two groups were statistically insignificant. Regarding in-hospital out come in group-I were hospital stay 5.28 ± 1.06 days, heart failure 28%, arrhythmia 8% and mortality was 2%. On the other hand in group-II hospital stay was 6.04±1.07 days, heart failure 68%, and arrhythmia 24% & mortality was 6%. All these were statistically significant between two groups except mortality. Conclusion: From this study it may be concluded that, left ventricular filling pressure assessed by Doppler echocardiograph predicts in-hospital outcome after acute ST segment myocardial infarction and prognosis is worse with increased left ventricular filling pressure. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22244 Cardiovasc. j. 2015; 7(2): 72-78